Patología neonatal en el hijo de madre adolescente, en el Hospital General Provincial Isidro Ayora, durante el año 2012. - Condolo Rojas, Gabriela Mariza (2013)
Over 16 million women aged 15 to 19 give birth each year in the world, 95% of these births occur in developing countries. There are several variables that influence the onset of parenthood in adolescence, making it difficult to unlink from each other. Teenage pregnancy has become a major public health problem, because they are basically cultural conditions which have led to a considerable increase in its prevalence, especially, poverty influence the likelihood that young women have become pregnant and if so enter a vicious circle. Teenage pregnancy is on the rise world increasingly appearing at earlier ages. Thus, in Ecuador has one of the highest rates of teenage pregnancy in Latin America, the second highest rate That is why in order to determine the main diseases that occur in children of adolescent mothers product, I decided to make this research work in which the percentage of teenage pregnancies in the Regional Hospital Isidro Ayora, in the year 2012, is 14% of all births. Determining the most at risk of teenage pregnancy is between 17-19 years old. Product Of the 388 births to teenage mothers, 337 newborns showed no pathology, accounting for 87%, 51 had pathology of these 41 cases of newborns had low birth weight, being the most common pathology.